2018
DOI: 10.1002/jcb.27918
|View full text |Cite
|
Sign up to set email alerts
|

miRNA‐155 and miRNA‐181a as prognostic biomarkers for pediatric acute lymphoblastic leukemia

Abstract: Mortality rates of acute lymphoblastic leukemia (ALL) have improved over the past 20 years; however, a significant portion of deaths stems from the lack of prognostic biomarkers, which can direct therapy and overcome drug resistance. microRNA‐155a (miRNA‐155a) and miRNA‐181a are two single‐stranded miRNAs involved in the pathogenesis of many types of leukemia and lymphoma and is linked to drug resistance. We investigated their expression levels in 55 patients, 45 diagnosed with ALL and 10 as a control group. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…The different expression of miR‐155 may affect the prognosis and may explain the resistance to the treatment pattern of HCV genotype 4 . On the other hand, studies that investigated the role of miR‐155 in CML and AML demonstrated that it is upregulated in cells and circulating exosomes . There was a negative correlation between the expression of miR‐155 and the response to antiviral drugs; however, a positive correlation with disease progression has been observed .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different expression of miR‐155 may affect the prognosis and may explain the resistance to the treatment pattern of HCV genotype 4 . On the other hand, studies that investigated the role of miR‐155 in CML and AML demonstrated that it is upregulated in cells and circulating exosomes . There was a negative correlation between the expression of miR‐155 and the response to antiviral drugs; however, a positive correlation with disease progression has been observed .…”
Section: Introductionmentioning
confidence: 99%
“…14 On the other hand, studies that investigated the role of miR-155 in CML and AML demonstrated that it is upregulated in cells and circulating exosomes. 4,[15][16][17] There was a negative correlation between the expression of miR-155 and the response to antiviral drugs; however, a positive correlation with disease progression has been observed. 18,19 Patients who achieved complete remission showed low levels of miR-155 in the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating miRNAs are attractive molecules as non-invasive cancer biomarkers due to their surprising degree of stability in biological fluids. Several recent studies have demonstrated that miRNAs are stably detectable in plasma/serum [28,29,30]. MiRNA-221 and miRNA-222 are overexpressed in different types of malignant neoplasms including ovarian cancer 31, hepatocellular cancer [32], glioblastomas [33] and breast cancer [10,13,34].…”
Section: Discussionmentioning
confidence: 99%
“…It has been evident that more than 10,000 discovered lncRNAs have been contributed to human solid and hematopoietic cancers [20].Adjacent with the high needs for new non-invasive diagnostic and prognostic biomarkers that target human cancer; the lncRNAs occupy the forefront of use in leukemia [19]. Recent studies provide evidence that the long non-coding RNA -HOTAIR "HOX transcript antisense RNA" has an oncogenic role in AML [2,18]; however; the precise underlying molecular mechanism still under investigations [21]. Few studies tried to determine the different pathways by which HOTAIR influence myelopoiesis; they reported that knockdown of HOTAIR blunted the expression of HOX1 and HOX4 during myeloid differentiation [19].…”
Section: Discussionmentioning
confidence: 99%
“…Micro RNAs (miRNA) are small non-coding RNA molecules, it's far composed approximately of (20-25nucleotides), they are corresponding for suppression gene expression via binding to complementary segments of messenger RNA and interfering with the formation of proteins by way of translation [13,[15][16][17][18]. According to Xing et al, miR-193a was downregulated in AML blasts because of hypermethylation in its promoter area.…”
Section: Introductionmentioning
confidence: 99%